Biomonitoring and Health Risk Assessment of Arsenic Contamination in Drinking Water among Rural Residents in Western Tehran. - Motahareh Harati; Seyed Mohammad Tabatabaei Jabali; Yousef Abdossalami Asl; Mahdi Chinichian; Tahereh Donyavi; Niloufar Bahari; Hadi Jalilvand; Negin Kassiri; Zahra Asadgol (PLoS ONE)
Arsenic is a widespread environmental contaminant that poses a significant threat to global health due to its toxicity and carcinogenicity. Given the high levels of arsenic found in the drinking water of western areas of Tehran, the objective of this study was to analyze levels of arsenic in multiple biological samples (blood, hair, and nails) collected from residents living in these areas. This cross-sectional study was conducted over three weeks in November 2022 in five villages. A total of 67 residents from these villages were included in the exposure group. Analysis of arsenic was carried out by using the Perkin Elmer Optima 8000 ICP-OES instrument coupled with the FIAS 100 flow injection module after sample digestion. The average concentration of arsenic in people's blood was 4.19 μg/l, which exceeds the standard limit of ATSDR (1 μg/l) by about 4 times. Additionally, 47.8% of blood samples exceeded the standard, while for nail and hair samples, the percentages were 22.4% and 13.4%, respectively. Water samples showed the highest percentage above the standard, with 67.2%. There is no significant relationship between arsenic levels in drinking water, hair and blood. However, a significant positive correlation was observed between the concentration of arsenic in drinking water and nail samples. The mean of hazard quotient (HQ) and carcinogenic risk (CR) indices of arsenic in drinking water suggest that the daily intake levels of the examined arsenic in the study area exceeded the acceptable thresholds ((HQ < 1) and (CR < 1 × 10-4)). Although this study demonstrated elevated arsenic exposure among the population in western Tehran, our findings showed no significant correlation between arsenic concentrations in drinking water and biological samples. Therefore, further research is required to identify other potential exposure pathways and develop targeted intervention strategies. Additionally, remediation measures to improve water quality remain essential in this rural area.